2015
DOI: 10.3390/molecules201219811
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Bioactivities of Novel Dichloro-Allyloxy-Phenol-Containing Pyrazole Oxime Derivatives

Abstract: Abstract:In this study, in order to find novel biologically active pyrazole oxime compounds, a number of dichloro-allyloxy-phenol-containing pyrazole oximes were designed and synthesized according to the method of active group combination. All of the target compounds were confirmed by 1 H-NMR, 13 C-NMR and elemental analysis. In addition, bioassays showed that all of the newly synthesized compounds had no acaricidal activity against Tetranychus cinnabarinus and low insecticidal activity against Aphis craccivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…In recent years, literature revealed that pyrazole derivatives had a wide range of biological activities, such as antibacterial [ 5 , 6 , 7 ], fungicidal [ 8 , 9 , 10 ], insecticidal [ 10 , 11 , 12 , 13 ], antiviral [ 14 , 15 ], and herbicidal [ 16 , 17 ] activities. In our previous work, we reported a series of pyrazole derivatives which had better insecticidal activity against Plutella xylostella [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, literature revealed that pyrazole derivatives had a wide range of biological activities, such as antibacterial [ 5 , 6 , 7 ], fungicidal [ 8 , 9 , 10 ], insecticidal [ 10 , 11 , 12 , 13 ], antiviral [ 14 , 15 ], and herbicidal [ 16 , 17 ] activities. In our previous work, we reported a series of pyrazole derivatives which had better insecticidal activity against Plutella xylostella [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxime ether has been extensively used as an active group in the structural optimization of agrochemical-related compounds. The commercial pesticides trifloxystrobin, cymoxanil, and enestroburin, also pictured in Figure , are successful oxime ether fungicides widely used in a variety of field crops . In this study, we designed the 3-position of coumarin containing an oxime ether group, evaluated the antifungal activity, and studied the relationship between the molecular structure and biological activity of oxime ether coumarin derivatives via three-dimensional quantitative structure–activity relationship (3D-QSAR) modeling.…”
Section: Introductionmentioning
confidence: 99%
“…将适量玉米叶在配好的药液中充分浸润后自然阴 干, 放入垫有滤纸的培养皿中, 接粘虫 3 龄中期幼虫 10 头/皿, 置于 24~27 ℃观察室内培养, 3 d 后调查结果. 以毛笔触动虫体, 无反应视为死虫, 并进行统计分析.3.3.2 目标化合物对苜蓿蚜和朱砂叶螨的杀虫活性采用浸渍法测定目标化合物对苜蓿蚜和朱砂叶螨 的杀虫活性[32] . 对于目标化合物用分析天平(0.0001 g) 称取一定质量的原药, 用含 1%吐温-80 乳化剂的 DMF 溶解配制成 1%母液, 然后用蒸馏水稀释备用, 每个处 理三个重复, 设空白对照, 阿维菌素作为对照药剂.…”
unclassified